THE NECESSITY OF CURRICULUM MANAGEMENT (American Journal of Research in Humanities and Social Sciences, 2023)
A curriculum is just a big learning plan. As new research is published and as practices change, we will be forced to make updates to curriculum content. ... You do it with a structured set of activities designed to assess and adjust your curriculum; in other words, with curriculum management.